2019
DOI: 10.3390/catal9121023
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Microbial Laccases: Patent Review of the Past Decade (2009–2019)

Abstract: There is a high number of well characterized, commercially available laccases with different redox potentials and low substrate specificity, which in turn makes them attractive for a vast array of biotechnological applications. Laccases operate as batteries, storing electrons from individual substrate oxidation reactions to reduce molecular oxygen, releasing water as the only by-product. Due to society’s increasing environmental awareness and the global intensification of bio-based economies, the biotechnologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 180 publications
(197 reference statements)
0
69
0
3
Order By: Relevance
“…Despite the potential of laccase-based biosensors as a sensitive analytical tool for phenolic compound detection, the commercial/industrial implementation of those devices is not available. This limitation is mostly due to laccase high production costs associated with isolation and purification processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential of laccase-based biosensors as a sensitive analytical tool for phenolic compound detection, the commercial/industrial implementation of those devices is not available. This limitation is mostly due to laccase high production costs associated with isolation and purification processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…1.10.3.2) oxidize a great variety of aromatic compounds [ 1 , 2 ]. They can be applied for wide industrial applications: organic synthesis, biosensor construction, biofuel cells development, biomass valorization, and xenobiotic biodegradation [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Typical laccases have four copper atoms, which form three different copper centers (type T1, T2 and T3) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…by authors in other topics. [12][13][14] In the present study, 174 homeopathy-related patents were found for the period analyzed. In an original way, the patents were analyzed by nationality and type of applicants.…”
Section: Wo2016011104 (A1) Gensco Lab Llc United Statesmentioning
confidence: 84%